Gender dan Ekologi dalam Pendidikan Indonesia Masa Orde Baru dan Pasca Reformasi: Perspektif Ekofeminisme - Setiyawan, Radius; Wahyuni, Holy Ichda (Humanis, 2023)
Gender and ecological issues are still a serious problem in Indonesia. This is evidenced by the high rate of violence against women and natural damage that occurs. Education is one sector that has the task of building gender and ecological awareness for every generation. Education has a periodization in the course of Indonesian history. This study aims to examine the value of ecological and gender education in the implementation of education during the New Orde and after reform eras. These two periods directly had a significant impact on gender and ecological education in Indonesia. The methodology in this study uses the library method using an ecofeminism perspective. This study is deliberately limited to only two periods of power, New Order and the Reformation Order. This was done so that this study could be focused and in-depth. The study in this paper will focus on explaining how gender and ecological awareness in education in Indonesia was socialized and internalized, both during the New Orde and after reformation eras